In vitro organogenesis, content phenols, and antioxidant capacity of two aluminum accumulator plant species from the Cerrado region, Brazil - Nogueira, Matheus Armelin [UNESP]; Marin, Vitor Rodrigues [UNESP]; Habermann, Gustavo [UNESP]; Cardoso, Jean Carlos (Springer Nature, 2023)
Aluminum (Al) is the most plentiful metal present in the Earth’s crust, and when present in acidic soils (pH < 5.0), it becomes soluble and toxic to most plant species. Species from acidic and aluminum-rich soil regions, such as Brazilian Cerrado, developed mechanisms allowing for their growth in these conditions. Some can accumulate Al in their tissues, especially in the leaves. However, the possible functions of Al in these plants are unknown. This study investigated the impact of Al on the organogenesis and production of phenolic compounds in extracts from cotyledonary leaf segments of two Al-accumulator species, Qualea grandiflora Mart. and Vochysia tucanorum Mart. (Vochysiaceae). The addition of Al at 320 μM in the absence of 6-benzylaminopurine (BAP) resulted in the regeneration of both species’ adventitious roots in cotyledonary leaf segments. In contrast, adding BAP without Al did not generate regeneration responses. However, shoot regeneration and development occurred when 0.44 and 0.88 μM BAP was added to the culture medium with 320.0 μM Al. Both species exhibited a noteworthy phenolic content, further enhanced by adding Al and, or, BAP. The antioxidant capacity of extracts also demonstrated a significant increase from the addition of Al and, or, BAP in both species. These findings have important significance for the cultivation and propagation of these species and demonstrate a close relationship between Al and the evolution of these plants. This study is the first to relate Al with phenolic content and antioxidant activity in these two Cerrado plant species, filling a gap in existing research.
Keywords: Adventitious shoots; Aluminum; Cytokinins; Organogenesis; Plant species